THE UNIQUENESS OF GENDER DISCOURSE EXPRESSION IN ENGLISH AND UZBEK LANGUAGES - Laylo Khasanova Abduakhat Kizi; Scientific Supervisor: G. I Narmurodova (Web of Journals Publishing, 2025)
This article explores the relationship between gender and language, focusing on how linguistic differences reflect societal roles and power dynamics. The study also delves into nonverbal communication, such as intonation, gestures, and body language, which further differentiate male and female speech. Through examples from both English and Uzbek languages, the article demonstrates how linguistic expressions and cultural norms shape gendered communication and influence social interactions.
Keywords: Gender, nonverbal, speech act, zoonyms, and paralinguistic element.